Integrated crop management practices for enhancing productivity, profitability, production-efficiency and monetary-efficiency of pigeonpea (Cajanus cajan) in Indo-Gangetic plains region - T, VARATHARAJAN; CHOUDHARY, ANIL K; POONIYA, VIJAY; DASS, ANCHAL; N, HARISH M (The Indian Journal of Agricultural Sciences, 2019)
It is concluded that CA-based integrated crop management (ICM) modules imbedded with zero-tillage and residue retention with proper combination of integrated nutrient, water and weed management practices as well as need based crop protection measures had higher crop productivity and profitability in pigeonpea over other conventional agriculture and organic agriculture-based ICM modules. Hence, the CA based module ICM7 as a complete ICM technology package [zero tillage–permanent raised bed + crop residue retention @ 3 t/ha + 100% RDF + (glyphosate-pre-plant followed by (fb) pendimethalinpre emergence fb imazethapyr-post emergence + 1 handweeding- mulch) + 2 irrigations + need based IPM/IDM] exhibited significantly higher productivity, profitability and resource-use efficiency over other conventional agriculture and organic agriculture based ICM modules in pigeonpea under semi-arid Indo-Gangetic plains region.